Aplikasi Antrian Pendaftaran Pasien Berbasis Desktop(Studi Kasus Di Puskesmas Karanggede) - Sutikno, Bambang; , Umi Fadlillah, ST. MEng (2017)
Karanggede Public Health Centre is an public health service located in Boyolali. As a Public Health Centre in a village, this public service implemented manual queue system (written documentation and announcement by the officer). This system caused various problems those are name missannouncing by the officer, the inequivalence of queue cards amount and the amount of the patient, and the long duration of the patients to take the queue cards. This research aims at creating queue application to overcome those problems. Method which is used in this research is System Development Life Cycle (SDLC). This application is build by the use of VB 6.0 programming language and MySQL database. The result of Blackbox testing shows that all the functions of the system run well. In line with this result the result of the questionnaires given to 15 persons shows the average score 67.8%. In conclusion, this application can operate the queue system well, effectively, and efficiently.